Iron Single Atom Catalyzed Quinoline Synthesis. Issue 34 (19th July 2021) - Chen, Zhongxin; Song, Jingting; Peng, Xinwen; Xi, Shibo; Liu, Jia; Zhou, Wenhui; Li, Runlai; Ge, Rile; Liu, Cuibo; Xu, Haisen; Zhao, Xiaoxu; Li, Haohan; et al.
Abstract: The production of high‐value chemicals by single‐atom catalysis is an attractive proposition for industry owing to its remarkable selectivity. Successful demonstrations to date are mostly based on gas‐phase reactions, and reports on liquid‐phase catalysis are relatively sparse owing to the insufficient activation of reactants by single‐atom catalysts (SACs), as well as, their instability in solution. Here, mechanically strong, hierarchically porous carbon plates are developed for the immobilization of SACs to enhance catalytic activity and stability. The carbon‐based SACs exhibit excellent activity and selectivity (≈68%) for the synthesis of substituted quinolines by a three‐component oxidative cyclization, affording a wide assortment of quinolines (23 examples) from anilines and acetophenones feedstock in an efficient, atom‐economical manner. Particularly, a Cavosonstat derivative can be synthesized through a one‐step, Fe1 ‐catalyzed cyclization instead of traditional Suzuki coupling. The strategy is also applicable to the deuteration of quinolines at the fourth position, which is challenging by conventional methods. The synthetic utility of the carbon‐based SAC, together with its reusability and scalability, renders it promising for industrial scale catalysis. Abstract : Iron single‐atom catalysts are developed for three‐component oxidative cyclization, affording a wide assortment of multifunctional quinolines and their deuterated derivatives (23 examples including Cavosonstat derivatives) from feedstock anilines and acetophenones.